Cº b<span>. </span>Points<span> on the </span>x<span>-axis ( </span>Y. 0)-7<span> (6 </span>2C<span>) are mapped to </span>points<span>. --IN- on the </span>y<span>-axis. ... </span>Describe<span> the transformation: 'Reflect A ALT if A(-5,-1), L(-</span>3,-2), T(-3,2<span>) by the </span>rule<span> (</span>x<span>, </span>y) → (x<span> + </span>3<span>, </span>y<span> + </span>2<span>), then reflect over the </span>y-axis, (x,-1) → (−x,−y<span>). A </span>C-2. L (<span>0.0 tº CD + ... </span>translation<span> of (</span>x,y) → (x–4,y-3)? and moves from (3,-6) to (6,3<span>), by how.</span>
Answer:
x > -8
Step-by-step explanation:
Divide both sides by -3 to get x by itself. Dividing by a negative number will switch the less-than symbol to a greater-than symbol. -3x ÷ -3 = x and 24 ÷ -3 = -8. When you put it all together, you get x > -8
Answer:
2
Step-by-step explanation:
Answer:
let the angles be 7x , 13x , 16x
7x + 13x + 16x = 180 ( sum of angles in a triangle is 180 degree)
36x = 180
x = 180 / 36
x = 5
therefore the angles are:
7 X 5 = 35 degree
13 X 5 = 65 degree
16 x 5 = 80 degree
plz mark me as the brainliest
I think the answer is 6 if i'm not mistaken.